Adolescent Pregnancy Midwifery Care for Mrs. D 17 years old at the Tanjung Sengkuang Community Health Center, Batam City - Mela Anjasari; Norma Jeepi Margiyanti; Nurul Huda (Jurnal Riset Ilmu Kesehatan Umum dan Farmasi (JRIKUF), 2024)
Teenage pregnancy is a pregnancy that occurs at a young age <20 years which is the result of sexual behavior either intentionally (married) or unintentionally (not married). Based on data from the Batam City Health Office for 2022 regarding reproductive health, it shows that teenage pregnancies are experienced by adolescents aged 15-18 years, namely 129 souls of the teenage target, namely 117,411 souls. Of the 21 puskesmas in Batam City, there are three puskesmas with the highest Teenage Pregnancy rate (≤20 years) obtained at the Tanjung Sengkuang puskesmas with 22.48% with 29 cases, Lubuk Baja 16.27% with 21 cases and Sei Lekop 10.85% with 14 cases. This Final Project aims to provide midwifery care for Adolescent Pregnancy at the Tanjung Sengkuang Health Center in Batam City in 2023. This case study method uses a descriptive method with a case study approach. Based on the results of the case study it can be concluded that Mrs. D, 17 years old G1P0A0, 31 weeks' gestational age with normal results of pregnancy care for 12 days, indicated by the good condition of the mother and fetus, the mother has accepted her pregnancy and has had her pregnancy checked at the health service. It is expected that the role of health workers is to detect the risk of complications in teenage pregnancy by being aware of emergency symptoms that require immediate action.